Relationship Marketing and Guanxi: A Case of Melody Shanghai Women’s Basketball Club - Zheng, Ying (2010)
This dissertation aims to demonstrate the roles of relationship marketing and guanxi in a non-profit organisation, Melody Shanghai Women’s Basketball Club, in Shanghai. The case study shows that for the western relationship marketing to work in the Chinese context, guanxi has to be incorporated. This is because in the Chinese context, guanxi is the prerequisite for doing business. Relationship marketing is strengthened with the integration of guanxi because guanxi involves ganqing that turns business relations into friendships. With strong ganqing and friendships, guanxi helps to retain people to Melody. This dissertation also finds out that due to the nature of the organisation, the guanxi in Melody is different than the conventional concept of guanxi studied in the past. Differences included: One, favours are not obligated to be returned. Two, the motive of creating guanxi is a less opportunistic one. Three, relationship does not always lead to immediate, direct exchange of goods. In short, the case study is a unique and extreme case that challenges both the conventional western concept of relationship marketing and the conventional concept of guanxi that have been studied in the past.